Introduction to Islamic law : Islamic law in theory and practice - Akgunduz, Ahmet, 1955- (Rotterdam : IUR Press, 2010)
The world today has become one large village. Muslims and non-Muslims live side by side and have to learn about one another, share commonalities and respect differences. At this time more than one and a half billion Muslims live in this village. Some of them are pious Muslims, trying to live in accordance with Islamic rules, whereas others do not while believing that these rules come from God (the Qur'an), from interpretations of His Messenger (the Sunnah) or the consensus of Muslim jurists (ijma'), and are at least rules derived via analogy (qiyas) from the main sources of Islam. Most Muslims think along these lines and agree with the above. The reader should remember that Muslim individuals should live according to Islamic rules in private, but no individual is responsible for implementing Islamic law. In any event, the need to learn the facts about Islamic law is necessary for Muslims as well as for non-Muslims if they live in the same society with Muslims, at least in the sense of general information. In any event, the need to learn the facts about Islamic law is necessary for Muslims as well as for non-Muslims if they live in the same society with Muslims, at least in the sense of general information. -- Publisher description.
Sharia, Fiqh, and Islamic law -- The sources of information for Islamic law (references) -- The historical periods of Islamic law -- Law (amali) schcools [sic] and theological schools (Itiqadi) in Islam (madhhabs) -- The period of Islamic law after the Turks professed Islam (960-1923) -- The modern period and Islamic law -- The system and methodology of Islamic law -- The implementation of Islamic law and its future.
'Islamitische Universiteit Rotterdam'--T.p. verso.
Includes bibliographical references (p. [359]-377) and index.
Keywords: Islamic law; Islamic law -- History